2,4-Dichlorobenzaldehyde 2,4-dinitrophenylhydrazone - Bao, Feng-yu (International Union of Crystallography, 2008)
The asymmetric unit of the title compound, C(13)H(8)Cl(2)N(4)O(4), contains two independent but similar and almost planar molecules. An intramolecular N—H⋯O hydrogen bond is observed in each molecule.